Specialized bilingual dictionaries for translators (some considerations for a user-oriented approach) - Gómez González-Jover, Adelina (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2005)
Given the strong demand for multilingual communication aimed at the transfer of research and investigation results of any kind to the dissemination of technological progress on a worldwide scale, specialized bilingual dictionaries are the main tools at the disposal of translators. Although it is generally accepted that dictionaries are to be user-oriented, i.e. designed for specific users, the underlying implications of such an obvious statement are not always taken into consideration. The aim of this paper is thus to present a brief explanation of some aspects that must be considered when carrying out a terminological work designed for a specific user: the mediator of interlinguistic communication.